Allele-Specific Silencing Ameliorates Restrictive Cardiomyopathy Attributable to a Human Myosin Regulatory Light Chain Mutation. Issue 9 (27th August 2019) - Zaleta-Rivera, Kathia; Dainis, Alexandra; Ribeiro, Alexandre J.S.; Cordero, Pablo; Rubio, Gabriel; Shang, Ching; Liu, Jing; Finsterbach, Thomas; Parikh, Victoria N.; Sutton, Shirley; Seo, Kinya; Sinha, Nikita; et al.
Abstract : Background: Restrictive cardiomyopathy is a rare heart disease associated with mutations in sarcomeric genes and with phenotypic overlap with hypertrophic cardiomyopathy. There is no approved therapy directed at the underlying cause. Here, we explore the potential of an interfering RNA (RNAi) therapeutic for a human sarcomeric mutation in MYL2 causative of restrictive cardiomyopathy in a mouse model. Methods: A short hairpin RNA (M7.8L) was selected from a pool for specificity and efficacy. Two groups of myosin regulatory light chain N47K transgenic mice were injected with M7.8L packaged in adeno-associated virus 9 at 3 days of age and 60 days of age. Mice were subjected to treadmill exercise and echocardiography after treatment to determine maximal oxygen uptake and left ventricular mass. At the end of treatment, heart, lung, liver, and kidney tissue was harvested to determine viral tropism and for transcriptomic and proteomic analysis. Cardiomyocytes were isolated for single-cell studies. Results: A one-time injection of AAV9-M7.8L RNAi in 3-day-old humanized regulatory light chain mutant transgenic mice silenced the mutated allele (RLC-47K) with minimal effects on the normal allele (RLC-47N) assayed at 16 weeks postinjection. AAV9-M7.8L RNAi suppressed the expression of hypertrophic biomarkers, reduced heart weight, and attenuated a pathological increase in left ventricular mass. Single adult cardiac myocytes from mice treated with AAV9-M7.8L showed partial restoration of contraction, relaxation, and calcium kinetics. In addition, cardiac stress protein biomarkers, such as calmodulin-dependent protein kinase II and the transcription activator Brg1 were reduced, suggesting recovery toward a healthy myocardium. Transcriptome analyses further revealed no significant changes of argonaute ( AGO1, AGO2 ) and endoribonuclease dicer ( DICER1 ) transcripts, and endogenous microRNAs were preserved, suggesting that the RNAi pathway was not saturated. Conclusions: Our results show the feasibility, efficacy, and safety of RNAi therapeutics directed towards human restrictive cardiomyopathy. This is a promising step toward targeted therapy for a prevalent human disease. Abstract : Supplemental Digital Content is available in the text.